Implementasi Sistem Keamanan Kendaraan dengan Sensor Fingerprint - Faizal Abdul Aziz; Hendri Setyawan; Bagus Esti Tomo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
In the modern era, the need for sophisticated vehicle security systems is increasing along with the high rate of motor vehicle theft. This research designs and implements a fingerprint sensor-based vehicle security system using an Arduino Uno microcontroller. This system aims to improve security by utilizing biometric technology that can only be accessed by verified users. The fingerprint sensor is used to recognize the user's fingerprint, then activate the system through a relay instead of a conventional key. System testing shows a fast response time with an estimated rise time of about 0.5 seconds and settling time of about 2 seconds, without any misidentification (false positive or false negative). Thus, the system is proven to provide higher security, good authentication speed, and ease of use compared to conventional security systems. These results show that the implementation of biometric technology in vehicles has the potential to be widely applied.